Cachexia research in Japan: facts and numbers on prevalence, incidence and clinical impact. Issue 5 (12th April 2016) - Konishi, Masaaki; Ishida, Junichi; Springer, Jochen; Anker, Stefan D.; von Haehling, Stephan
Abstract: Even though most clinical data on cachexia have been reported from Western countries, cachexia may be a growing problem in Asia as well, as the population in this area of the world is considerably larger. Considering the current definitions of obesity and sarcopenia in Japan, which are different from the ones in Western countries, the lack of a distinct cachexia definition in Japan is strinking. Only one epidemiological study has reported the prevalence of cachexia using weight loss as part of the definition in patients with stage III or IV non‐small cell lung cancer. Although the reported prevalence of 45.6% is within the range of that in Western countries (28–57% in advanced cancer), we cannot compare the prevalence of cachexia in other types of cancer, heart failure, chronic obstructive pulmonary disease (COPD), and kidney disease (CKD) between Japan and Western countries. In patients with heart failure, one third of Japanese patients has a body mass index <20.3 kg/m 2 whereas the prevalence of underweight is 13.6% in reports from Western countries. These results may suggest that there are more cachectic heart failure patients in Japan, or that using the same definition like Western countries leads to gross overestimation of the prevalence of cachexia in Japan. The rate of underweight patients in COPD has been reported as 31–41% in COPD and seems to be high in comparison to the prevalence of cachexia in Western countries (27–35%). The reported lowest quartile value of BMI (19.6 kg/m 2 ) in CKD may match with the prevalence of cachexia in Western countries (30–60%). The number of clinical trials targeting cachexia is very limited in Japan so far.